Robotic total knee arthroplasty safely reduces length of stay in an Asian public healthcare system - Kai C. A. Chan; Amy Cheung; Ping-Keung Chan; Michelle H. Luk; Kwong Y. Chiu; Henry Fu (Bone & Joint Open)
Aims: Around the world, the emergence of robotic technology has improved surgical precision and accuracy in total knee arthroplasty (TKA). This territory-wide study compares the results of various robotic TKA (R-TKA) systems with those of conventional TKA (C-TKA) and computer-navigated TKA (N-TKA). Methods: This is a retrospective study utilizing territory-wide data from the Clinical Data Analysis and Reporting System (CDARS). All patients who underwent primary TKA in all 47 public hospitals in Hong Kong between January 2021 and December 2023 were analyzed. Primary outcomes were the percentage use of various robotic and navigation platforms. Secondary outcomes were: 1) mean length of stay (LOS); 2) 30-day emergency department (ED) attendance rate; 3) 90-day ED attendance rate; 4) 90-day reoperation rate; 5) 90-day mortality rate; and 6) surgical time. Results: A total of 8,492 knees from 7,746 patients were included in the study. Overall robotic use had risen to 20.4% (2023 Q3 to Q4: 355/1,738) by the end of 2023, with Mako being the most popular at 10.3% (179/1,738). R-TKA had the shortest mean LOS compared with N-TKA and C-TKA (5.5 vs 6.3 and 7.1 days, respectively; p < 0.001). Only Mako (9.7%) demonstrated reduced 90-day ED attendance compared to C-TKA (13.1%; p = 0.009), Cori/Navio (15.0%; p = 0.005), and Rosa (16.4%; p < 0.001). No differences in 90-day reoperation rate and mortality were observed between all groups. Mean surgical times were longer in R-TKA groups by 20.6 minutes (p < 0.001). Conclusion: R-TKA use has increased in recent years, and has been shown to reduce hospital stay despite having a slightly longer surgical time, proving a promising candidate to alleviate the burden on healthcare systems. Individual differences between R-TKA systems contributed to variable clinical outcomes. Cite this article: Bone Jt Open 2024;6(1):12–20.